Cybersecurity Awareness and Digital Minimalism towards Cyber Fraud Prevention in Generation Z - Indah Dwi Novianti; Anis Chariri (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The increasing adoption of digital banking among Generation Z has also heightened the risk of cybercrime, particularly cyber fraud. This study aims to analyze the influence of Cybersecurity Awareness and Digital Minimalism on Cyber Fraud Prevention, using a quantitative approach and the Protection Motivation Theory (PMT) framework. Data were collected through an online questionnaire from 77 Generation Z respondents who use digital banking services and were analyzed using multiple linear regression. The findings reveal that both independent variables positively and significantly affect cyber fraud prevention. These results suggest that enhancing digital security awareness and managing digital usage consciously can strengthen efforts to prevent cybercrime. This study contributes to the development of behavior-based prevention strategies and advances the field of digital forensic accounting.